Public policies on obesity: a literature review of global challenges and response strategies - Lan, Xiaoyue; Sulaiman, Norhasmah (Springer Science and Business Media LLC, 2024)
As a complex and multifactorial health problem, obesity results from the interaction of genetic, environmental, dietary, and lifestyle factors. Globally, the increase in obesity and related chronic diseases has been associated with global trade liberalization, rapid urbanization, and economic growth. This article is a narrative literature review on the global obesity problem and explores the global challenges of obesity and strategies to address them. The research methodology included a retrieval of peer-reviewed articles, including PubMed, ScienceDirect, and Google Scholar. Specific search terms like “obesity”, “policy”, “nutrition”, and “global”, outline the impact of obesity on global health and social systems, as well as policy effectiveness and gaps that exist. The outcome reveals regional differences in obesity rates and provides an analysis of the policies that countries have implemented to address obesity and their effectiveness, in particular concerning improving the quality of diets and limiting the intake of added sugars. Despite some policies proving effective, the challenge of obesity is far from being fully addressed, necessitating robust international efforts and strategies.